2002
DOI: 10.1088/0029-5515/42/7/315
|View full text |Cite
|
Sign up to set email alerts
|

Predictive capability of MHD stability limits in high performance DIII-D discharges

Abstract: Results from an array of theoretical and computational tools developed to treat the instabilities of most interest for high performance tokamak discharges are described. The theory and experimental diagnostic capabilities have now been developed to the point where detailed predictions can be productively tested so that competing effects can be isolated and either eliminated or confirmed. The predictions using high quality discharge equilibrium reconstructions are tested against the observations for the princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 66 publications
(146 reference statements)
2
39
0
Order By: Relevance
“…13͒ and DCON. 14 It has been shown that ideal MHD instabilities can be accurately reproduced 15 for DIII-D discharges with good quality internal equilibrium profile data and magnetic probe data, as is typically available for the discharges discussed here. Both codes show that the equilibrium is stable to all low n modes.…”
Section: Stability Analysismentioning
confidence: 79%
“…13͒ and DCON. 14 It has been shown that ideal MHD instabilities can be accurately reproduced 15 for DIII-D discharges with good quality internal equilibrium profile data and magnetic probe data, as is typically available for the discharges discussed here. Both codes show that the equilibrium is stable to all low n modes.…”
Section: Stability Analysismentioning
confidence: 79%
“…The nominal no-wall limit is ≈ 4 times the dimensionless internal inductance, l i , during an I p flat-top period, and ≈ 2.4 times l i for an I p ramp-up period for DIII-D discharges aimed at high performance [34]. In this article the purpose of comparing b N with a no-wall limit is simply to indicate that observed SOLCs may be relevant to an AT, not as a precise delineation of discharge regimes.…”
Section: Operating Regimesmentioning
confidence: 99%
“…DIII-D is a highly non-circular tokamak 11 that has carried out a wide variety of seminal studies of tokamak stability 12,13 . The interpretation of these experiments depends critically on understanding the anomalies in the applied fields and how the plasma interacts with them.…”
Section: Introductionmentioning
confidence: 99%